Remains of Copper Alloy Vessels from the Medieval Knightly Residence in Mierzyn, Central Poland - Piotr Strzyż (Fasciculi Archaeologiae Historicae)
During investigations carried out at the site of a late medieval knightly residence in Mierzyn (Piotrków Trybunalski District, Central Poland), archaeologists discovered, among other things, numerous fragments of three-legged vessels cast from copper alloy, known as ‘Grapens.’ They were used for cooking and reheating food. The collection obtained from the above-mentioned site comprises 13 fragments from several different vessels, which distinguishes Mierzyn from other motte type knightly residences in Poland. In the course of research, including specialist analyses, at least four vessels were identified based on the discussed fragments. They varied in appearance – there were both classic forms with bulbous bodies and fitted with characteristic handles and legs, but also a form similar to cauldrons or frying pans – with a sleeve for a wooden handle. The fact that a fairly diverse assortment of metal Grapens was used at the excavated site testifies to the material status of the representatives of the knightly Nagodzice family of Mierzyn.